Young aspiring globals (YAGs): early-stage strategies of knowledge-focused international entrepreneurs. Issue 6 (26th August 2021) - Brockman, Paul; Dow, Douglas; Phan, Hoang Long; Rammal, Hussain Gulzar; Zurbruegg, Ralf
Abstract : Purpose: This study aims to explore the intention–action relationship of small and medium-sized (SMEs) firms with knowledge capital that declare their intention to internationalize from their inception. Design/methodology/approach: The authors apply the theory of planned behavior and hand-collect a database of Chinese born globals, purely domestic firms and traditional exporting firms. The authors' hypothesis is that Chinese born globals [or young aspiring globals (YAGs)] will strive to acquire domestic and international patents at an early stage to institutionally protect their knowledge-capital via intellectual property rights as they enter the competitive global marketplace. Findings: The results confirm that knowledge-focused YAGs apply for patents at an earlier stage than purely domestic and traditional exporting firms. However, in the long run, these firms are neither demonstrating increased knowledge capital by being more innovative nor producing more valuable innovations than their counterparts. Originality/value: This study tests the intention–action relationship in the context of SMEs internationalization. It contributes to the internationalization literature by identifying the internationalization pattern of born globals (YAGs) from emerging markets and providing an explanation for what happens to these firms as they mature.